Kesan bencana banjir di Kelantan terhadap kesejahteraan psikologi sukarelawan - Nur Hafizah Md Akhir; Azlinda Azman; Noremy Md Akhir (Penerbit Universiti Kebangsaan Malaysia, 2018)
Flooding is a crisis situation that may cause damage to the property, deaths and risks to human well-being. Flood victims may suffer from lack in comfort, property damage, loss of income and psychological conditions. In addition, poor psychological conditions may not only be suffered by the victims but also the volunteers. This is because volunteers play an important role and carry a responsibility in the process of providing assistance to flood victims before, during and after the disaster. The lack of psychological support may lead to the disruption of volunteer’s well-being, and thus affecting the efficiency of service delivery. Problems faced by the volunteers require immediate action before they become serious. Therefore, this study was conducted to explore problems encountered by volunteers who were directly involved in the flood disaster relief mission in Kelantan in 2014. A qualitative case study was carried out in this study. The purposive sampling technique was used to select 27 participants, and in-depth interviews were conducted to volunteers who met the prescribed sampling criteria. The results revealed that health, safety, stress and psychological disturbances were problems faced by participants. In this paper, however, researcher focuses on exploring psychological disturbances and how this affect volunteer’s well-being.